JIDOR SENTULAN: SEJARAH, MEDIA DAKWAH, DAN IDENTITAS LOKAL JOMBANG - Li'ila Nur Ainiyah; Hendra Afiyanto (IAIN Bengkulu, 2023)
This study seeks to analyze the origins of Jidor Sentulan which was used as a da'wah media and as the identity of the Jombang district. By analyzing Jidor Sentulan in Jombang, can answer the first formulation, what is the history of Jidor Sentulan art in Jombang? Second, how is Jidor Sentulan used as a media of da'wah and how is the procession performed in Jombang? Third, how can the process of Jidor Sentulan become a local identity and what are the analogical characteristics of Jidor Sentulan's art? The historical method is used as an analytical tool which consists of four stages including heuristics, verification, interpretation, and historiography. In the process of collecting data, this study used library research and interview techniques. The findings in this study are, first, the beginning of the existence of Jidor Sentulan in Jombang was brought by one of the followers of the Diponegoro Army, namely mbah Suhadak. Second, Jidor Sentulan is used as a symbol of Islam in marriage and has eight stages of events. Third, Jidor Sentulan is a local identity from Jombang Regency which has an analogical character in its performance. Kajian ini berupaya menganalisis awal mula adanya Jidor Sentulan yang digunakan sebagai media dakwah dan sebagai identitas kabupaten Jombang. Dengan menganalisis Jidor Sentulan di Jombang, maka dapat menjawab rumusan pertama, bagaimana sejarah kesenian Jidor Sentulan di Jombang? Kedua, bagaimana Jidor Sentulan digunakan sebagai media dakwah dan bagaimana prosesi pementasannya di Jombang? Ketiga, bagaimana proses Jidor Sentulan bisa menjadi identitas lokal dan bagaimana karakteristik analogis pada kaesenian Jidor Sentulan? Metode sejarah digunakan sebagai alat analisisnya yang terdiri dari empat fase termasuk heuristik, verifikasi, interpretasi, dan historiografi. Teknik pencarian literatur dan wawancara digunakan dalam proses pengumpulan data penelitian ini. Hasil temuan dalam penelitian ini, pertama, awal mula adanya Jidor Sentulan di Jombang dibawa oleh salah satu pengikut dari Laskar Diponegoro yaitu Mbah Suhadak. Kedua, Jidor Sentulan dijadikan sebagai syiar Islam dalam pernikahan dan memiliki delapan tahapan peristiwa. Ketiga, Jidor Sentulan merupakan identitas lokal dari Kabupaten Jombang yang memiliki karakter analogi dalam pementasannya.